2022
DOI: 10.3390/su14052929
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Mechanism and Influencing Factors of the Coordinated Development of Economy and Environment in China’s Resource-Based Cities

Abstract: In order to explore how to achieve the coordinated development of the economy and environment, this paper uses the logistic model to verify that the city economy and the environment can achieve coordinated symbiosis. Next, an evaluation index system was used as empirical testing in order to measure the performance of the economy and environment. Further, the degree of coupling and coordination between them was obtained, and an econometric model was used to find the factors that affect the coordination and symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Step 2: Calculate Indicator Weights. The main principle of entropy method is that the more weight the indicator value has, the more important the indicator is [22]. 12 International Journal of Energy Research Calculate contribution of the j year under the indicator P ij .…”
Section: Entropy Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2: Calculate Indicator Weights. The main principle of entropy method is that the more weight the indicator value has, the more important the indicator is [22]. 12 International Journal of Energy Research Calculate contribution of the j year under the indicator P ij .…”
Section: Entropy Weightmentioning
confidence: 99%
“…Coupling degree C only reflects the degree of mutual influence between systems. We used the coupling coordination degree D to study the degree of coupling coordination between STI, HE, and CE systems [24].…”
Section: Entropy Weightmentioning
confidence: 99%
“…On the other hand, the coupling between HQD and RECC subsystems can be distilled into interactions between society, economy, resources, and environment. Scholars have studied the economic-resource (Chen and Chen, 2019), economicenvironmental (Li et al, 2022), economic-ecological (Liao et al, 2019), economic-energy-environmental (Wang et al, 2020), economic-resource-environmental (Zhu et al, 2020), socio-economic-environmental (Yang et al, 2015), and socioeconomic-ecological (Wan et al, 2021;Bao et al, 2022) perspectives. Most of the studies on these issues are empirical studies covering multiple countries and provinces, and they all demonstrate the interconnectedness of subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2022b). The coordination evaluation was achieved by using models such as coupling models (Li et al, 2022), system dynamics (Bao et al, 2022), and structural equation models (Chen and Chen, 2019). However, no scholars have carried out research from the level of HQD and RECC.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars found that the annual average population and industrial wastewater discharge are the main factors contributing to the coupling coordination relationship between the economy and environment in resource-based cities. Resource-based cities usually rely on their urban resource endowments in their early economic development [ 52 ]. In addition, with the deepening and expansion of research, coupling analyses based on two, three [ 53 ], and four systems [ 54 ] have been conducted.…”
Section: Introductionmentioning
confidence: 99%